2021
DOI: 10.3390/su13031500
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Keeping Alive Sustainable Foraging Practices: Wild Vegetables and Herbs Gathered by Afghan Refugees Living in Mansehra District, Pakistan

Abstract: The issue of foraging for wild food plants among migrants and relocated communities is an important one in environmental studies, especially in order to understand how human societies rearrange their practices linked to nature and how they adapt to new socioecological systems. This paper addresses the complexity of Traditional/Local Environmental Knowledge (LEK) changes associated to wild vegetables and herbs across four different groups of Afghan refugees living in Mansehra District, NW Pakistan, since 1985. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The overharvesting of underground parts or whole plants should be discouraged, especially in the case of threatened species, as this practice causes elimination and dwindling of the plant’s status in the wild [ 43 , 63 ]. Our findings are also supported by Ahmad et al [ 64 ], Sharif et al [ 65 ], Siddique et al [ 66 ], Anwer et al [ 67 ], and Manduzai et al [ 68 ] from the Pakistan Himalayas; and Debbarma et al [ 45 ] and Krupa et al [ 69 ] from India. Asif et al [ 28 ] and Haq et al [ 48 ] from the Kashmiri Himalayas, India; Pala et al [ 46 ] from the Eastern Himalayas; Singh et al [ 70 ] from the Western Himalayas, India; and Tiwari et al [ 71 ] from the Kumaun Himalayas, India.…”
Section: Resultssupporting
confidence: 90%
“…The overharvesting of underground parts or whole plants should be discouraged, especially in the case of threatened species, as this practice causes elimination and dwindling of the plant’s status in the wild [ 43 , 63 ]. Our findings are also supported by Ahmad et al [ 64 ], Sharif et al [ 65 ], Siddique et al [ 66 ], Anwer et al [ 67 ], and Manduzai et al [ 68 ] from the Pakistan Himalayas; and Debbarma et al [ 45 ] and Krupa et al [ 69 ] from India. Asif et al [ 28 ] and Haq et al [ 48 ] from the Kashmiri Himalayas, India; Pala et al [ 46 ] from the Eastern Himalayas; Singh et al [ 70 ] from the Western Himalayas, India; and Tiwari et al [ 71 ] from the Kumaun Himalayas, India.…”
Section: Resultssupporting
confidence: 90%
“…In the case of Zumand, the element of freedom was completely absent, as people were relocated with brutal force, overnight, and put into unhospitable and unknown environments, destroying the safety net of the community. We observed similar symptoms of trauma among the Kurds of Azerbaijan, who were relocated from the mountain region to the plains of inland Azerbaijan during the armed conflict in Nagorny Karabakh (Pieroni and Sõukand 2016) and among Afgani migrants in Pakistan (Manduzai et al 2021).…”
Section: The Trauma Of Forced Relocationsupporting
confidence: 57%
“…On this matter, some authors (among them [ 7 ]) have argued that sometimes the health policies of host countries substantially follow assimilationist principles, according to which migrating communities should adopt the ideas and habits of the majority group of the host society. Recently, some authors of this paper [ 8 ] suggested that the prolonged stay of Afghan Pathans in refugee camps in Mansehra District, Pakistan may lead to the erosion of their LEK related to wild food plants and herbs, as exposure to natural resources is very restricted in the camps. In order to further investigate this issue, we decided to look in more detail at the overall ethnobotany of Afghan refugees in Kohat District, NW Pakistan.…”
Section: Introductionmentioning
confidence: 99%